Uji Keefektivitas Sedatif Hipnotik Ekstrak Daun Keji Beling (Strobilanthes Crispus) terhadap Gangguan Tidur (Insomnia) pada Mencit - Immanuella Pinem; Muhammad Chairul; Boyke Marthin Simbolon (Jurnal Anestesi, 2025)
This study aimed to evaluate the sedative-hypnotic effectiveness of keji beling leaf extract (Strobilanthes crispus) on sleep disturbances (insomnia) in mice. The method employed was an experimental design with a completely randomized design (CRD). The study subjects were healthy male mice aged 2–3 months with body weights of 20–30 grams, divided into five treatment groups: negative control, positive control (diazepam), and three groups with EEDKB doses (100 mg/Kg BW, 300 mg/Kg BW, and 500 mg/Kg BW). The fireplace test method was used to assess sleep activity. Data were analyzed using a One Way ANOVA test. The results indicated a significance value of 0.000 (< 0.05), suggesting significant differences in sedative-hypnotic effectiveness among the control and treatment groups. In conclusion, EEDKB demonstrated significant sedative effects, with effectiveness increasing proportionally to the dosage